2012 and 2016 Parliamentary Elections ın Georgia: Paralles, Challenges and Outcomes - Givi Amiranashvili (European Scientific Journal, ESJ, 2017)
The paper provides an overview on the political and electoral aspects of the pre-election campaigns of the 2012 and 2016 parliamentary elections in Georgia. The author compares the pre-election atmospheres and draws a parallels between the pre-election campaigns for the 2012 and 2016 parliamentary elections. Author provides a critical analyses of the legislative amendments made in 2012. He argues that these amendments mostly stipulated political situation and the pre-election environment even tenser and inflicted serious harm to free and competitive pre-election environment in 2012. In this regards, the paper refers in particular to the examples of these particular amendments. The author analyses the nature of the 2016 election campaign and argues that is was held in a peaceful environment, was competitive and largely calm and in comparison with the 2012 elections, the trend towards improvement is obvious. In this context, he provides the international observer organizations’ reports and statements about the 2016 elections. In the conclusion, the author provides some recommendations on how the pre-election environment and the election legislation might be improved and harmonized in accordance with international standards.